2015
DOI: 10.1515/sg-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

How small and constrained is the genome size of angiosperm woody species

Abstract: Angiosperm hardwood species are generally considered to show an average smaller genome size with a narrow range of variation than their herbaceous counterparts. Various explanations pertaining to limitations of cell size exerted by wood fibers, the requirement of smaller stomata, longer generation time, large population size, etc., have been put forward to account for their small and constrained genome size. Yet studies done in the past several years show that genomically as well as evolutionarily, hardwoods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 121 publications
0
4
1
Order By: Relevance
“…We also report the transcriptome assembly of S. cumini for the first time in this study. We inferred S. cumini genome to be tetraploid in this study, whereas previous studies have also shown the existence of intraspecific polyploidy (ranging from 2x to 6x) in S. cumini species (Ohri, 2015;Sharma et al, 2020). The phylogenetic position of S. cumini was resolved with respect to 17 other Eudicot orders, and comparative evolutionary analyses showed the key plant secondary metabolism pathways, such as the phenylpropanoid-flavonoid (PF) biosynthesis pathway, were adaptively evolved in this Syzygium species, which are responsible for the immense medicinal properties of this tree.…”
Section: Introductioncontrasting
confidence: 46%
See 1 more Smart Citation
“…We also report the transcriptome assembly of S. cumini for the first time in this study. We inferred S. cumini genome to be tetraploid in this study, whereas previous studies have also shown the existence of intraspecific polyploidy (ranging from 2x to 6x) in S. cumini species (Ohri, 2015;Sharma et al, 2020). The phylogenetic position of S. cumini was resolved with respect to 17 other Eudicot orders, and comparative evolutionary analyses showed the key plant secondary metabolism pathways, such as the phenylpropanoid-flavonoid (PF) biosynthesis pathway, were adaptively evolved in this Syzygium species, which are responsible for the immense medicinal properties of this tree.…”
Section: Introductioncontrasting
confidence: 46%
“…It is only the third and till date the largest genome to be sequenced from the largest tree genus containing approximately 1,200 species. S. cumini was previously reported to show intraspecific polyploidy compared to S. aromaticum and S. grande ( Ohri, 2015 ). Our analyses using two independent approaches to estimate the genomic ploidy also confirmed the tetraploidy in S. cumini genome.…”
Section: Discussionmentioning
confidence: 98%
“…Remarkably, besides the classic examples of Sequoia sempervirens and Fitzroya cupressoides, a very high incidence of polyploidy has been reported in Ephedra (76.0 %) and Juniperus (22.3 %) as also the recent discovery of spontaneous production and sustenance of various polyploid forms under cultivation in Ginkgo (Smarda et al 2018). In sharp contrast to this angiosperm hardwoods not only show high basic numbers resulting from paleopolyploidy but also have well-developed polyploid series and complex dysploid number variation across various families and genera (Ohri 2015). Dysploidy is also observed in some gymnosperm taxa e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the hardwoods which show extensive inter-and intraspecific polyploid series and palaeoploidy (Ohri 2015), gymnosperms possess a very narrow range of somatic chromosome numbers (2n=14-66), conserved karyotypes within various families and genera Ohri 2020 a,b, Ohri 2021b) and rare instances of recent polyploidy (Khoshoo 1959, Ahuja 2005, Ohri, 2021a. Only some genera like Zamia, Pseudotsuga, Pseudolarix, Prumnopitys, Halocarpus, Podocarpus exhibit dysploid numbers Ohri 2020a, Ohri 2021b).…”
Section: Discussionmentioning
confidence: 99%